Formation of a specific biological cycle in young skiers-racers and biathletes 11-15 years, depending on the level and direction of physical activity - Utkina, A. (Slobozhanskyi herald of science and sport, 2019)
The article presents the results of the analysis of the ratio of the training process according to the types of training and the performed cyclic physical activity and their influence on the formation of a specific biological cycle in female skiers-racers and biathletes 11-15 years old at the initial training stage and preliminary basic training.